A purified and lyophilized Pseudomonas aeruginosa derived pyocyanin induces promising apoptotic and necrotic activities against MCF-7 human breast adenocarcinoma - Ahmed A. Abdelaziz; Amal M. Abo Kamer; Khaled B. Al-Monofy; Lamiaa A. Al-Madboly (Microbial Cell Factories, 2022)
Abstract Background Pyocyanin, a specific extracellular secondary metabolite pigment produced by Pseudomonas aeruginosa, exhibits redox activity and has toxic effects on mammalian cells, making it a new and potent alternative for treating cancer. Breast cancer (BC) treatment is now defied by acquired and de novo resistance to chemotherapy, radiation, or targeted therapies. Therefore, the anticancer activity of purified and characterized pyocyanin was examined against BC in our study. Results The maximum production of pyocyanin (53 µg/ml) was achieved by incubation of the highest pyocyanin-producing P. aeruginosa strain (P32) in pH-adjusted peptone water supplemented with 3% cetrimide under shaking conditions at 37 °C for 3 days. The high purity of the extracted pyocyanin was proven by HPLC against standard pyocyanin. The stability of pyocyanin was affected by the solvent in which it was stored. Therefore, the purified pyocyanin extract was lyophilized to increase its shelf-life up to one year. Using the MTT assay, we reported, for the first time, the cytotoxic effect of pyocyanin against human breast adenocarcinoma (MCF-7) with IC50 = 15 μg/ml while it recorded a safe concentration against human peripheral blood mononuclear cells (PBMCs). The anticancer potential of pyocyanin against MCF-7 was associated with its apoptotic and necrotic activities which were confirmed qualitatively and quantitively using confocal laser scanning microscopy, inverted microscopy, and flow cytometry. Caspase-3 measurements, using real-time PCR and western blot, revealed that pyocyanin exerted its apoptotic activity against MCF-7 through caspase-3 activation. Conclusion Our work demonstrated that pyocyanin may be an ideal anticancer candidate, specific to cancer cells, for treating MCF-7 by its necrotic and caspase-3-dependent apoptotic activities.